2010
DOI: 10.1007/s00011-010-0205-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory actions of serine protease inhibitors containing the Kunitz domain

Abstract: Recent studies have demonstrated that the Kunitz inhibitors are not only protease inhibitors, but can also prevent inflammation and tissue injury and subsequently promote tissue remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 81 publications
1
34
0
6
Order By: Relevance
“…Bikunin is a Kunitz-type protease inhibitor [11] and a structural component of extracellular matrix [12]. Bikunin is the common subunit of a group of protein/carbohydrate complexes that constitute plasma proteins of the inter--inhibitor family [13].…”
Section: Expressionmentioning
confidence: 99%
“…Bikunin is a Kunitz-type protease inhibitor [11] and a structural component of extracellular matrix [12]. Bikunin is the common subunit of a group of protein/carbohydrate complexes that constitute plasma proteins of the inter--inhibitor family [13].…”
Section: Expressionmentioning
confidence: 99%
“…To counter-regulate the effect of these proteases, several protease inhibitors are produced by the liver in the presence of inflammation; these include acute phase reactants such as α 1 -antitrypsin and proteins of the inter-α-inhibitor family [9]. Urinary trypsin inhibitor is one such important protease inhibitor found in human blood and urine; it has been also referred to in the literature as ulinastatin or bikunin [10, 11]. It is an acidic glycoprotein (molecular weight 30 kDa) and Kunitz-type serine protease inhibitor composed of 143 amino acid residues and includes two Kunitz-type domains [7, 10].…”
Section: Introductionmentioning
confidence: 99%
“…As compared to wild-type mice, mortality due to experimental sepsis is higher in genetically modified knockout mice that lack the genes for synthesis of urinary trypsin inhibitor [11, 13]. Several preclinical studies have shown a reduction in the systemic inflammatory response and organ dysfunction due to sepsis in animals treated with ulinastatin [1317].…”
Section: Introductionmentioning
confidence: 99%
“…Ulinastatin is one a serine protease inhibitor in the multifunctional Kunitz family found in human blood and urine 3. Basic research showed that ulinastatin had anti‐inflammatory activity through suppressing neutrophil accumulation and activation and inhibiting secretion of inflammatory cytokines 3.…”
Section: Introductionmentioning
confidence: 99%
“…Basic research showed that ulinastatin had anti‐inflammatory activity through suppressing neutrophil accumulation and activation and inhibiting secretion of inflammatory cytokines 3. Clinical studies also reported that anti‐inflammatory activity of ulinastatin decreased the mortality of SIRS conditions, such as sepsis4, 5 and acute respiratory distress syndrome 6.…”
Section: Introductionmentioning
confidence: 99%